Long-term Outcome With Prolonged Use of Interferon-alpha Administered Intermittently for Metastatic Renal Cell Carcinoma: A Phase II Study - Kankuri-Tammilehto Minna; Perasto Laura; Pyrhönen Seppo; Salminen Eeva (Greece, 2025)
Background/aim: Interferon-alpha (IFN-alpha) has shown survival benefits in metastatic renal cell carcinoma (mRCC), but the knowledge about long-term outcome is sparse. Additional knowledge is beneficial because IFN-alpha usage in combination therapy such as immune checkpoint inhibitor for mRCC is an area of interest. This is the longest follow-up concerning IFN-alpha treatment.
Patients and methods: A total of 117 metastatic renal cell cancer (mRCC) patients without prior chemotherapy were enrolled between 1994-2002 and followed-up until January 2022. The median follow-up was 18 months. After progression to IFN-alpha, the patients were not treated with tyrosine kinase, mTOR inhibitors or bevacizumab as these were not standard therapies at that time or the patients' performance status was too poor. Mean treatment duration was 11 months.
Results: Median overall survival was 19.0 months, 5-year survival rate 16.2%, and 10-year survival rate 9.0%. There were statistically significant differences in survival in response to treatment (log-rank test, p<0.001): median overall survival was 52.0 months for objective responses, 25.0 months for stable disease and 5.0 months for progressive disease. Proportion of 5-year survivors was 29% in low, 20% in intermediate, and 7% in high-risk groups, respectively (p=0.001).
Conclusion: With prolonged INF-alpha treatment stable and responding patients can obtain late objective responses, long-lasting complete responses, and long-term outcome with acceptable toxicity. IFN-alpha is an alternative therapy when multiple treatment lines are used for mRCC and an interesting option to study for combined therapies such as immune checkpoint inhibitor-based therapies.